Significados la muerte e inmigración en la película Biutiful - Petrescu, Olivia Narcisa (Acta Hispanica, 2015)
Starting from the hermeneutics ofthe plot identifiable in the movie Biutiful,directed by the Mexican Alejandro GonzálezIñárritu in 2010, our study aims to analyse themulticultural connections among the characters,in terms of their tragic destinies, of thedeath, illegal immigration and poverty in anunusual framework as it is that of a sordid andmarginal Barcelona.Even if the story concernsonly a film, one could embody multipleintertextual references which allude to fantasyliterature. Besides, the harsh reality and theanxieties experienced by the main protagonistestablish a credible insight of some real ethnic,social and spiritual phenomena, specific forXXI century Europe, but also universal for allages of humanity. From this perspective, ourexegesis is meant to be a cultural interpretationof the life-death significance, as perceivedthrough three crisscrossing communities in themotion picture: the Spanish, Chinese, andSenegalese communities, which metaphoricallyrepresent three very different continents andcultures.